Design of an Autonomous Orchard Navigation System Based on Multi-Sensor Fusion - Zhengquan Su; Wei Zou; Changyuan Zhai; Haoran Tan; Shuo Yang; Xiangyang Qin (Agronomy)
To address the limitations of traditional GNSS-based navigation systems in orchard environments, we propose a multi-sensor fusion-based autonomous navigation method for orchards. A crawler-type agricultural platform was used as a test vehicle, and an autonomous orchard navigation system was constructed using a 2D LiDAR, a dynamic electronic compass, and an encoder. The proposed system first filters LiDAR point cloud data and uses the DBSCAN–ratio–threshold method to process data and identify clusters of tree trunks. By matching the center coordinates of trunk clusters with a fruit tree distribution map, the platform’s positional measurements are determined. An extended Kalman filter fusion algorithm is then employed to obtain a posterior estimate of the platform’s position and pose. Experimental results demonstrate that in localization accuracy tests and navigation tests, the proposed system provides high navigation accuracy and robustness, making it suitable for autonomous walking operations in orchard environments.